The World Bank Group, the IMF and human rights : a contextualized way forward / Willem Van Genugten. - Genugten, Willem J. M. van (Intersentia, 2015)
Includes Guiding Principles on the World Bank Group, the International Monetary Fund and Human RightsThe World Bank Group and the International Monetary Fund are under substantial pressure to accept more accountability under international human rights law. This publication sets out the standards by which these international financial institutions are bound under international human rights law as it currently stands.Human rights law is 'living law' and has changed over time, as have international financial institutions, despite their sometimes static approach to their own mandates. However, the World Bank Group and the International Monetary Fund are both starting to recognize more and more the relevance of human rights to the fulfilment of their respective mandates, even if they still maintain, be it to different degrees, that international human rights law is only partly applicable to them. This publication argues that this position is no longer tenable and that human rights law does in fact apply to both international financial institutions.